A controlled randomized clinical trial to assess postoperative analgesia after thiopental–isoflurane anaesthesia or total intravenous anaesthesia with alfaxalone in dogs. Issue 3 (21st January 2019) - Bennell, Paula M.; Whittem, Ted; Tudor, Elizabeth
Abstract: Alfaxalone, a synthetic neuroactive steroid, has been attributed with properties including sedation, anaesthesia and analgesia. The clinical relevance of any analgesic properties of alfaxalone has not been demonstrated. This study was a prospective, blinded, randomized, negative control clinical trial in 65 healthy dogs presented for ovariohysterectomy. Anaesthesia was induced and maintained, for Group 1 (TIVA) dogs ( n  = 30) with intravenous alfaxalone alone and for Group 2 dogs ( n  = 35) with thiopental followed by isoflurane in 100% oxygen inhalation. After ovariohysterectomy, quantitative measures of pain or nociception were recorded at 15 min intervals for 4 hr using three independent scoring systems, a composite measure pain scale (CMPS), von Frey threshold testing and measures of fentanyl rescue analgesia. The mean CMPS scores of Group 2 (THIO/ISO) dogs remained higher than Group 1 (TIVA) dogs from 15 to 135 min post‐surgery but this difference was not statistically significant. There were no significant differences between groups in the proportions of dogs requiring rescue fentanyl analgesia, the total fentanyl dose used or the time to first fentanyl dose. The Von Frey threshold testing was found to be unsuitable for measurement of pain in this experimental model. When administered as total intravenous anaesthesia, alfaxalone did not provide analgesia in the postoperative period.